Changing trends of adverse pregnancy outcomes with maternal age in primipara with singleton birth: A join point analysis of a multicenter historical cohort study in China in 2011‐2012. (1st May 2019) - Zhang, Xiaolei; Xu, Huangfang; Hu, Rong; Xiong, Yu; Gu, Weirong; Zhou, Qiongjie; Li, Xiaotian
Abstract: Introduction: Adverse pregnancy outcomes are related to two opposite maternal factors, youth and aging. However, the change in trend of specific outcomes with childbearing age is unknown. The aim of this study was to investigate the changing trend of various maternal and neonatal outcomes with maternal age from 17 to 44 years. Material and methods: Data were extracted from the medical records from 2011‐2012 of 39 public hospitals of 14 cities in China. The eligibility criteria were primiparity and singleton birth. Join point regression analysis was used to estimate the percent change per year of age (PCA) to explore the trends of adverse pregnancy outcomes with regard to maternal age and to identify the join point of maternal age when the trend was changed. Results: A total of 89 171 women were eligible for analysis. There were four categories of trend styles. Continuously increasing trends were linear for placenta previa (PCA, 0.1%), placenta implantation (PCA, 0.09%) and postpartum hemorrhage (PCA, 0.22%), and nonlinear for gestational diabetes mellitus with one join point of 23 years (PCA, 0.17% and 0.71%) and cesarean section with four join points of 25, 28, 31 and 36 years (PCA, 1.39%, 0.34%, 1.51%, 3.49% and 0.94%). Continuously decreasing trends were linear for intrahepatic cholestasis (PCA, −0.02%) and nonlinear for anemia with one join point of 28 years (PCA, −0.49% and −0.04%). The bidirective trends were downward to upward for preterm birth (PCA, −2.93%, −0.36% and 0.38%), hypertension in pregnancy (PCA, −0.09%, 0.47%), low birthweight (PCA 0.51% and 0.38%), low 1‐minute Apgar score (PCA, −0.28% and 0.07%), low 5‐minute Apgar score at (PCA, −0.10% and 0.06%) and neonatal intensive care unit admission (PCA, −1.92%, −0.07% and 0.12%) with a nadir age of 28 years. The bidirective trend was upward to downward for macrosomia (PCA, 0.39% and −0.11%), with a peak age of 30 years. Conclusions: The changes in the trend of specific outcomes were different with maternal age, which means that youth, aging or both could affect the outcomes.